Potential relationship between cuproptosis and sepsis-acquired weakness: an intermediate role for mitochondria - Yang, Luying; Xie, Leiyu; Li, Min; Miao, Yanmei; Yang, Jun; Chen, Shaolin; Ma, Xinglong; Xie, Peng (Frontiers in Physiology, 2025)
Sepsis is defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection. Skeletal muscle atrophy due to critical illness is a common phenomenon in the intensive care unit (ICU) and is referred to as ICU-acquired weakness (ICU-AW). The occurrence of ICU-AW in patients with sepsis is known as sepsis-acquired weakness (SAW). Furthermore, it is well known that maintaining normal muscle function closely relates to mitochondrial homeostasis. Once mitochondrial function is impaired, both muscle quality and function are affected. Copper plays a key role in mitochondrial homeostasis as a transition metal that regulates the function and stability of various enzymes. Copper is also involved in oxidation-reduction reactions, and intracellular copper overload causes oxidative stress and induces cell death. Previous studies have shown that excess intracellular copper induces cell death by targeting lipid-acylated proteins that regulate the mitochondrial tricarboxylic acid (TCA) cycle, which differs from the known canonical mechanisms of regulated cell death. Furthermore, inhibitors of cell death, such as apoptosis, necroptosis, pyroptosis and ferroptosis, are not effective in preventing copper-induced cell death. This new form of cell death has been termed “Cuproptosis”; however, the mechanism by which copper-induced cell death is involved in SAW remains unclear. In this paper, we review the possible relationship between cuproptosis and SAW. Cuproptosis may be involved in regulating the pathological mechanisms of SAW through mitochondria-related signaling pathways, mitochondria-related ferroptosis mechanisms, and mitochondria-related genes, and to provide new ideas for further investigations into the mechanism of SAW.